An extended π-conjugated area of electron-donating units in D–A structured polymers towards high-mobility field-effect transistors and highly efficient polymer solar cells. Issue 11 (2nd March 2017) - Cai, Ping; Chen, Zhenhui; Zhang, Lianjie; Chen, Junwu; Cao, Yong
Abstract : Two D–A conjugated polymers, FBT-DThDT -1T andFBT-DThDT -TT, were synthesized and applied in field-effect transistors and inverted polymer solar cells. Abstract : Two D–A conjugated polymers, FBT-DThDT -1T andFBT-DThDT -TT, using 5, 6-difluoro-2, 1, 3-thiadiazole (FBT) as the electron-accepting unit, and terthiophene or 2, 5-di(thiophen-2-yl)thieno[3, 2- b ]thiophene as the electron-donating unit, respectively, were synthesized. Among them, the first batch ofFBT-DThDT -TT with relatively low molecular weight (MW) can be denoted asFBT-DThDT -TT-L and the second batch ofFBT-DThDT -TT with much higher MW can be denoted asFBT-DThDT -TT-H .FBT-DThDT -1T possesses a low FET hole mobility of 2.6 × 10 −3 cm 2 (V s) −1 and a poor power conversion efficiency (PCE) of 0.91% in inverted polymer solar cells (i-PSCs) under the illumination of AM1.5G, 100 mW cm −2 light. Compared withFBT-DThDT -1T, FBT-DThDT -TT with extended π-conjugation bears a TT replacing the middle thiophene of terthiophene on the backbone, which would increase the coplanarity of the polymer and thus facilitate both intermolecular packing and charge transport.FBT-DThDT -TT shows strong interchain aggregation in a room temperature solution, its absorption spectra in a room temperature solution and in a thin film were almost identical. The field-effect transistors based onFBT-DThDT -TT-L andFBT-DThDT -TT-H show improved hole mobilities of 0.38 and 0.20 cm 2 (V s) −1, respectively. The i-PSCs based onFBT-DThDT -TT-L show a better PCE of 3.47%, and the i-PSCs based onFBT-DThDT -TT-H with a higher MW exhibit the best PCE up to 7.78%, with highly improved absorption capacity and miscibility with PC71 BM. Moreover, with a 355 nm thick active layer, a PCE of 6.72% with a high FF of 67.8% is still obtained forFBT-DThDT -TT-H -based devices. The impressive results makeFBT-DThDT -TT a promising candidate for applications of large-scale solution-processable PSCs.